Third order derivative spectrophotometric determination of ascorbic acid in fruits and vegetables - Ozgur, MU; Sungur, S (ELSEVIER, 1995)
Ascorbic acid (AA) has been determined in kiwi, parsley and grapefruit by third order derivative spectrophotometry without using any separation or background correction techniques and reagents. The method is based on the measurement of the distances between two extremum values (peak-to-peak amplitudes) in the third order derivative spectra of the extracts. A metaphosphoric acid (3% w/v)-acetic acid (8% v/v) mixture was found to be the most suitable extraction solution. In the third order derivative spectrum, the extrema of 259.4 nm and 276.2 nn were used for the quantitative determination of AA in kiwi, and the extrema of 227 nm and 237 nm were used for the quantitative determination of AA in parsley and grapefruit. Calibration curves were constructed for the 2.0-10.0 mu g ml(-1) concentration range. Relative standard deviations were calculated from the assay results of 14 samples. They were found to be in the ranges of 0.53-2.45% and 0.50-1.41% for the proposed method and the Association of Official Analytical Chemists (AOAC) method, respectively. The obtained results were statistically compared with those of the official method of AOAC using the F test. There was no significant difference between the precisions at a 95% confidence level.
Keywords: ascorbic acid; fruits; derivative spectrophotometry; LIQUID-CHROMATOGRAPHIC DETERMINATION; SOFT DRINKS; VITAMIN-C; JUICES; FOODS; ASSAY; Chemistry